2015
DOI: 10.1007/s40495-015-0041-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the COX-2 Pathway to Improve Therapeutic Response in the Obese Breast Cancer Patient Population

Abstract: Multiple studies have demonstrated that obesity is associated with a worse outcome for all breast cancer subtypes and that obese breast cancer patients do not respond as well as normal weight patients to aromatase inhibitor treatment and chemotherapy. While a number of mechanisms have been proposed to explain this link, recent studies have provided evidence that elevated local cyclooxygenase-2 (COX-2) expression and the resulting increase in prostaglandin E2 (PGE2) production may play an important role. COX-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…Moreover, the negative impacts of rs689466 variant genotypes or haplotype *4 on disease-free survival of breast cancer patients were dependent on the menopausal status, being detected only in postmenopausal women. Such findings appear to reinforce the role of local aromatase induction and the consequent estradiol production by breast adipose tissue after menopause, which can be induced by elevated COX2 and PGE2 in inflamed breast tissue of obese women (Bowers & deGraffenried 2015).…”
Section: Figuresupporting
confidence: 67%
See 2 more Smart Citations
“…Moreover, the negative impacts of rs689466 variant genotypes or haplotype *4 on disease-free survival of breast cancer patients were dependent on the menopausal status, being detected only in postmenopausal women. Such findings appear to reinforce the role of local aromatase induction and the consequent estradiol production by breast adipose tissue after menopause, which can be induced by elevated COX2 and PGE2 in inflamed breast tissue of obese women (Bowers & deGraffenried 2015).…”
Section: Figuresupporting
confidence: 67%
“…Such deleterious effect of rs689466 on prognosis, however, was valid only for obese patients, suggesting that its action may depend on the availability of stimulating factors, probably released within the obesity-related inflammatory process. Accordingly, obesity has been associated with increased circulating levels of several growth factors, cytokines and adipokines, including interleukin-6, an inflammatory Endocrine-Related Cancer cytokine secreted by both immune cells and adipocytes, which have been shown to promote PGE2 production via its effects on COX2, resulting in elevated aromatase levels and estrogen production in the breast tissue (Bowers et al 2015). Moreover, the negative impacts of rs689466 variant genotypes or haplotype *4 on disease-free survival of breast cancer patients were dependent on the menopausal status, being detected only in postmenopausal women.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, selective COX-2 inhibition has been suggested to be potentially capable of preventing or delaying diabetic neuropathy [14]. In clinical studies, Laura et al demonstrated that, in the breast tissue of obese women, a higher concentration of circulating cytokines promotes greater macrophage COX-2 expression and produces more PGE 2 [15]. These observations indicate that COX-2-mediated inflammation substantially contributes to relevant complications in subjects with metabolic syndrome and diabetes, further strengthening the importance of COX-2 activation in the development of obesity and obesity-related complications.…”
Section: Cox-2-derived Pgs and Obesity Associated Complicationsmentioning
confidence: 99%
“…NSAIDs are acting on biological processes altered both by primary tumor surgery, as described above, and by adiposity. For instance, it has been suggested that adiposity could induce COX-2 expression by the macrophages and tumor cells (19) and promote angiogenesis (20)(21)(22). We therefore hypothesized that breast cancer patients with an elevated BMI would have an increased benefit from intra-operative NSAIDs.…”
mentioning
confidence: 98%